PTFE (Polytetrafluoroethylene) composite emulsion and membrane filter material
By adding bentonite and other additives to the PTFE composite emulsion, the negative impact of emulsion aggregation phenomenon on the filtration performance of the filter material is solved, and a more uniform emulsion distribution and higher filtration accuracy are achieved.
Patent Information
- Application Number
- CN202411609854.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, emulsion aggregation is prone to occur during bonding on the substrate, which affects the filtration performance of the filter material.
Add bentonite to the polytetrafluoroethylene dispersion and combine myristate and nonionic surfactant to optimize the emulsion aggregation phenomenon and improve the pore size distribution and filtration accuracy of the filter material.
By adding bentonite and other additives, the emulsion aggregation phenomenon is effectively avoided, and the uniformity of the emulsion on the substrate fibers and the filtration accuracy of the filter material are improved.
Smart Images

Figure CN119455528A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of filter materials, and in particular relates to a PTFE composite emulsion and a membrane-coated filter material. Background Art
[0002] In order to improve the filtering effect, a soft film of polymer material is covered on the surface of the substrate to form a coated filter material, which is a common method to improve the filtering accuracy of the filter material. In order to smoothly bond the PTFE membrane to the substrate, the substrate needs to be impregnated to attach a layer of coating agent to the surface of the substrate. This coating agent has a certain bonding effect, which can make the PTFE membrane easier to be compounded on the substrate.
[0003] The commonly used impregnation liquid is a polytetrafluoroethylene dispersion. Since the coating process is after the impregnation, after the substrate is impregnated with the polytetrafluoroethylene dispersion, emulsion coagulation will inevitably occur. This emulsion coagulation phenomenon that occurs on several substrate fibers or between fibers will have a certain negative impact on the filtering performance of the filter material, such as affecting the uniformity and consistency of the airflow inside the prepared filter material. Summary of the invention
[0004] In view of the above technical problems, the present application proposes a PTFE composite emulsion and a membrane filter material, and the specific technical solutions are as follows:
[0005] The first aspect of the present application is to provide a PTFE composite emulsion, comprising a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion, wherein the polytetrafluoroethylene dispersion comprises polytetrafluoroethylene, a silane coupling agent and deionized water, and the amount of bentonite added is 0.02 to 0.05 wt % of the polytetrafluoroethylene.
[0006] Furthermore, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 20-45%.
[0007] Furthermore, the amount of bentonite added is 0.03wt% of polytetrafluoroethylene.
[0008] Furthermore, myristic acid ester and nonionic surfactant are also included.
[0009] Furthermore, the addition amount of the myristic acid ester is 0.75-1.4% of polytetrafluoroethylene, and the addition amount of the nonionic surfactant is 3-5 times that of the myristic acid ester.
[0010] Furthermore, the amount of myristic acid ester added is 1.1% of polytetrafluoroethylene.
[0011] Furthermore, the added amount of the nonionic surfactant is 4 times that of myristic acid ester.
[0012] Furthermore, the nonionic surfactant is selected from polyoxyethylene alkylphenol ethers.
[0013] The second aspect of the present application is to provide a membrane filter material, wherein the membrane filter material is obtained by impregnating a substrate in the PTFE composite emulsion described in any one of claims 1 to 8 and then curing the substrate.
[0014] Furthermore, the membrane filter material also has a PTFE membrane layer outside.
[0015] The beneficial effects of the present invention are as follows: after adding bentonite to the polytetrafluoroethylene dispersion in the present application, it is found through microscopic detection that the linear coagulation of the emulsion on the fiber of the substrate impregnated with it can be effectively avoided, and the uniformity of the emulsion distribution on the substrate fiber can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Shown is a SEM image of the filter material prepared in Example 2;
[0017] Figure 2 Shown is a SEM image of the filter material prepared in Comparative Example 1;
[0018] Figure 3 Shown is the pore size distribution of the filter material prepared in Comparative Example 1;
[0019] Figure 4 The pore size distribution of the filter material prepared in Example 2 is shown;
[0020] Figure 5 Shown is the pore size distribution used to prepare the filter material in Example 5;
[0021] Figure 6 The pore size distribution of the filter material prepared in Example 6 is shown;
[0022] Figure 7 Shown is the pore size distribution used to prepare the filter material in Example 7;
[0023] Figure 8 Shown is the pore size distribution used to prepare the filter material in Example 8;
[0024] Fig. 9 Shown is the pore size distribution used to prepare the filter material in Example 9;
[0025] Fig.10 Shown is the pore size distribution of the filter material prepared in Example 10;
[0026] Fig.11 Shown is the pore size distribution used to prepare the filter material in Example 11;
[0027] Fig.12The pore size distribution of the filter material prepared in Example 12 is shown;
[0028] Fig.13 Shown is the pore size distribution used to prepare the filter material in Example 13;
[0029] Fig.14 Shown is the pore size distribution of the filter material prepared in Comparative Example 4;
[0030] Fig.15 Shown is the pore size distribution of the filter material prepared in Comparative Example 5;
[0031] Fig.16 Shown is the pore size distribution of the filter material prepared in Comparative Example 6;
[0032] Fig.17 The pore size distribution of the filter material prepared in Comparative Example 7 is shown. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments.
[0034] Low resistance coated filter media
[0035] Low-resistance coated filter material is a high-efficiency filter material formed by impregnating the substrate in PTFE composite emulsion and then hot-pressing the surface to form a film. Due to the dense PTFE film layer on the surface of the coated filter material, surface filtration is achieved, and the gaps are small, and the resistance is relatively stable. The surface of ordinary uncoated filter material is ordinary fiber. With the infiltration of dust particles, the resistance increases steadily at first, and the growth rate is faster in the later period, tending to rise, indicating that the dust cleaning performance of the filter material will be reduced in the later period, resulting in increased dust cleaning resistance and deepening of aging.
[0036] The base material is made of fibers through the existing production process of opening, blending, carding, laying, pre-needling, main needling, and felting. The base material generally uses synthetic fibers, or synthetic fibers mixed with glass fibers. Among them, synthetic fibers are mainly polyester, polypropylene, polyamide, and polytetrafluoroethylene. In the exhaust gas treatment in power plants and other fields, polytetrafluoroethylene will be preferentially used to make the base material fiber to ensure durability in a certain degree of high temperature and acid-base mixed gas.
[0037] PTFE composite emulsion is a composite emulsion mainly composed of polytetrafluoroethylene and supplemented by myristic acid ester, and is mixed with silane coupling agent, non-ionic surfactant, bentonite and deionized water. The polytetrafluoroethylene, silane coupling agent and deionized water together constitute a polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 20-45%, and the addition amount of silane coupling agent is 0.2-2% of polytetrafluoroethylene.
[0038] In some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 20%, the amount of silane coupling agent added is 0.2% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the amount of silane coupling agent added is 0.2% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 30%, the amount of silane coupling agent added is 0.5% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 30%, the amount of silane coupling agent added is 0.5% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 30%, the amount of silane coupling agent added is 0.5% of polytetrafluoroethylene, and the balance is water The content is 35%, the amount of silane coupling agent added is 1% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 40%, the amount of silane coupling agent added is 1% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 45%, the amount of silane coupling agent added is 1% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 45%, the amount of silane coupling agent added is 1.5% of polytetrafluoroethylene, and the balance is water; in some embodiments, the solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 45%, the amount of silane coupling agent added is 2% of polytetrafluoroethylene, and the balance is water;
[0039] By adding bentonite to the polytetrafluoroethylene dispersion, it is used to effectively improve the phenomenon of emulsion coagulation on the surface of the substrate fiber between the two processes after the substrate is impregnated and the surface is coated, and the uniformity of the emulsion on the surface of the substrate fiber is improved. The amount of bentonite added is 0.02-0.05% of the mass of polytetrafluoroethylene, and the particle size of the bentonite is required to be 50-200nm.
[0040] In some embodiments, the amount of bentonite added is 0.02% of the mass of polytetrafluoroethylene, and the particle size range of bentonite is D10=50nm, D90=80nm; in some embodiments, the amount of bentonite added is 0.03% of the mass of polytetrafluoroethylene, and the particle size range of bentonite is D10=70nm, D90=100nm; in some embodiments, the amount of bentonite added is 0.04% of the mass of polytetrafluoroethylene, and the particle size range of bentonite is D10=100nm, D90=200nm; in some embodiments, the amount of bentonite added is 0.05% of the mass of polytetrafluoroethylene, and the particle size range of bentonite is D10=120nm, D90=200nm.
[0041] In the implementation scheme, by adding myristic acid ester and nonionic surfactant, it is found that the improvement effect on the emulsion coagulation phenomenon after adding bentonite can be optimized. More specifically, the pore size distribution state of the filter material is optimized, the uniformity and consistency of the pore size distribution are improved, and then the filtration accuracy is improved.
[0042] In some embodiments, the amount of myristate added is 0.75-1.4% of polytetrafluoroethylene, and the amount of nonionic surfactant added is adjusted according to the amount of myristate added. Generally speaking, the amount of nonionic surfactant added is 3-5 times that of myristate. For example, the amount of myristate added is 0.75% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 3 times that of myristate; for example, the amount of myristate added is 0.9% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 3 times that of myristate; for example, the amount of myristate added is 1.1% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 4 times that of myristate; for example, the amount of myristate added is 1.3% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 4 times that of myristate; for example, the amount of myristate added is 1.4% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 5 times that of myristate; for example, the amount of myristate added is 1.4% of polytetrafluoroethylene, and the amount of nonionic surfactant added is 3 times that of myristate.
[0043] The nonionic surfactant is selected from polyoxyethylene alkylphenol ethers, such as polyoxyethylene octylphenol ether, polyoxyethylene nonylphenol ether, polyoxyethylene dodecylphenol ether, polyoxyethylene isooctylphenol ether, and polyoxyethylene phenol ether.
[0044] In the present application, unless otherwise specified, the addition amount "%" refers to the weight percentage.
[0045] Example 1
[0046] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.02% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0047] Example 2
[0048] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.03% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0049] Example 3
[0050] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.04% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0051] Example 4
[0052] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.05% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0053] Comparative Example 1
[0054] The polytetrafluoroethylene dispersion has a polytetrafluoroethylene solid content of 25%, a silane coupling agent added in an amount of 1% of the polytetrafluoroethylene, and the rest is deionized water. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain a PTFE composite emulsion.
[0055] Comparative Example 2
[0056] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.06% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0057] Comparative Example 3
[0058] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion and bentonite added to the polytetrafluoroethylene dispersion. The polytetrafluoroethylene solid content in the polytetrafluoroethylene dispersion is 25%, the added amount of a silane coupling agent is 1% of the polytetrafluoroethylene, the rest is deionized water, and the added amount of bentonite is 0.01% of the polytetrafluoroethylene. The above components are mixed and then subjected to conventional dispersion treatment methods such as stirring and ultrasound to obtain the PTFE composite emulsion.
[0059] Performance Testing
[0060] The polytetrafluoroethylene substrate was immersed in the polytetrafluoroethylene impregnation solution obtained in Examples 1 to 4 and Comparative Examples 1 to 3, and then dried at 150° C. for 60 seconds, 280° C. for 60 seconds, and 380° C. for 60 seconds to obtain a polytetrafluoroethylene filter material.
[0061] The polytetrafluoroethylene filter materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were characterized by SEM and Figure 1 and Figure 2 The SEM images of Example 2 and Comparative Example 1 are shown respectively. Figure 1 and Figure 2 It is not difficult to find that when conventional polytetrafluoroethylene dispersion without bentonite is used to impregnate the substrate, a large area of polytetrafluoroethylene dispersion agglomeration occurs in the obtained polytetrafluoroethylene filter material, including adhesion between fibers after the polytetrafluoroethylene dispersion solidifies, and a large area of polytetrafluoroethylene dispersion agglomerates remain in the interlaced parts of the fibers. However, when the PTFE composite emulsion with bentonite added is used to impregnate the substrate, the obtained polytetrafluoroethylene filter material does not have this phenomenon. Figure 2 The agglomeration phenomenon of the polytetrafluoroethylene dispersion in a larger area is reduced; and through a large number of experiments in the present application, it is found that the appropriate addition amount of bentonite is 0.02-0.05% of the polytetrafluoroethylene. Within this range, the addition of bentonite can effectively improve the agglomeration phenomenon of the polytetrafluoroethylene dispersion. A lower or higher addition amount will make the effect worse, and among them, the best effect is achieved when the addition amount of bentonite is 0.03% of the polytetrafluoroethylene, and the agglomeration phenomenon of the polytetrafluoroethylene dispersion is almost unobservable.
[0062] Example 5
[0063] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of the silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 0.75% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0064] Example 6
[0065] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 0.9% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0066] Example 7
[0067] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0068] Example 8
[0069] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0070] Example 9
[0071] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.2% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0072] Example 10
[0073] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.3% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0074] Embodiment 11
[0075] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.4% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0076] Example 12
[0077] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 4 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0078] Example 13
[0079] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 5 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0080] Comparative Example 4
[0081] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of the silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 0.6% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After the above components are mixed, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0082] Comparative Example 5
[0083] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.5% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 3 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0084] Example 6
[0085] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 2.5 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0086] Example 7
[0087] The PTFE composite emulsion includes a polytetrafluoroethylene dispersion, and bentonite, myristate, and polyoxyethylene nonylphenol ether added to the polytetrafluoroethylene dispersion. The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 25%, the added amount of silane coupling agent is 1% of the polytetrafluoroethylene, and the rest is deionized water. The added amount of bentonite is 0.03% of the polytetrafluoroethylene, the added amount of myristate is 1.1% of the polytetrafluoroethylene, and the added amount of polyoxyethylene nonylphenol ether is 5.5 times that of myristate. After mixing the above components, conventional dispersion treatment methods such as stirring and ultrasound are used to obtain the PTFE composite emulsion.
[0088] Performance Testing
[0089] The polytetrafluoroethylene substrate was immersed in the polytetrafluoroethylene impregnation solution obtained in Examples 5 to 13 and Comparative Examples 4 to 7, and then dried at 150° C. for 60 seconds, 280° C. for 60 seconds, and 380° C. for 60 seconds to obtain a polytetrafluoroethylene filter material.
[0090] The polytetrafluoroethylene filter materials prepared in Examples 5 to 13 and Comparative Examples 4 to 7 were characterized by SEM, and no obvious agglomeration of the polytetrafluoroethylene dispersion was observed, indicating that the newly added myristic acid ester and polyoxyethylene nonylphenol ether had no obvious negative effect on the improvement of bentonite.
[0091] The pore size distribution of the polytetrafluoroethylene filter materials prepared in Example 2, Examples 5 to 13, Example 1, and Comparative Examples 4 to 7 was tested by mercury intrusion porosimetry to obtain different pore size distribution state results. Figure 3 to Figure 17 They correspond to the pore size distributions of the following examples respectively.
[0092] Figure 3 : Comparative Example 1;
[0093] Figure 4 : Embodiment 2;
[0094] Figure 5 : Embodiment 5;
[0095] Figure 6 : Embodiment 6;
[0096] Figure 7 : Embodiment 7;
[0097] Figure 8 : Embodiment 8;
[0098] Fig. 9 : Embodiment 9;
[0099] Fig.10 : Embodiment 10;
[0100] Fig.11 : Embodiment 11;
[0101] Fig.12 : Embodiment 12;
[0102] Fig.13 : Embodiment 13;
[0103] Fig.14 : Comparative Example 4;
[0104] Fig.15 : Comparative Example 5;
[0105] Fig.16 : Comparative Example 6;
[0106] Fig.17 : Comparative example 7.
[0107] Combination Figure 3 to Figure 17 It can be found that the pore size distribution of the filter material impregnated with polytetrafluoroethylene dispersion is concentrated above 0.8μm, and the pore size distribution is wide; while the pore size distribution of the filter material impregnated with PTFE composite emulsion with bentonite added is concentrated below 0.8μm, the pore size distribution is narrower and more concentrated, and more than half of the pore size is 0.6μm; further, with the increase of the addition amount of myristic acid ester, the pore size distribution is narrower, and the proportion of micropores with a pore size of 0.6μm exceeds 70%, and the optimal addition amount of myristic acid ester is 1.1%; when the addition amount of myristic acid ester is relatively fixed, the optimal addition amount of polyoxyethylene alkylphenol ether is four times that of myristic acid ester, and the addition of myristic acid ester is more conducive to the pore size of the filter material being concentrated at 0.6μm, thereby improving the filtration accuracy.
[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them.
Claims
1. PTFE composite emulsion, characterized in that, The invention comprises a polytetrafluoroethylene dispersion and bentonite added into the polytetrafluoroethylene dispersion. The polytetrafluoroethylene dispersion comprises polytetrafluoroethylene, a silane coupling agent and deionized water. The addition amount of the bentonite is 0.02-0.05wt% of the polytetrafluoroethylene.
2. The PTFE composite emulsion according to claim 1, characterized in that The solid content of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 20-45%.
3. The PTFE composite emulsion according to claim 1, characterized in that The amount of bentonite added is 0.03 wt % of polytetrafluoroethylene.
4. The PTFE composite emulsion according to claim 1, characterized in that Also included are myristate esters and nonionic surfactants.
5. The PTFE composite emulsion according to claim 4, characterized in that The added amount of the myristic acid ester is 0.75-1.4% of polytetrafluoroethylene, and the added amount of the nonionic surfactant is 3-5 times of the myristic acid ester.
6. The PTFE composite emulsion according to claim 5, characterized in that The amount of myristic acid ester added is 1.1% of polytetrafluoroethylene.
7. The PTFE composite emulsion according to claim 5, characterized in that The addition amount of the nonionic surfactant is 4 times that of myristic acid ester.
8. The PTFE composite emulsion according to claim 5, characterized in that The nonionic surfactant is polyoxyethylene alkylphenol ether.
9. The membrane filter material is characterized in that: The membrane filter material is obtained by impregnating a substrate in the PTFE composite emulsion described in any one of claims 1 to 8 and then curing the substrate.
10. The membrane filter material according to claim 9, characterized in that: The membrane filter material also has a PTFE membrane layer outside.
Citation Information
Cited By
Fluorine-free high-flux anti-adhesion fiber membrane filtering material and preparation method thereof
CN122164150A